Метод расчета индукции магнитного поля линий электропередачи на основе цилиндрических пространственных гармоник - Ерисов, Анатолий Васильевич; Пелевина, Екатерина Дмитриевна; Пелевин, Дмитрий Евгеньевич (НТУ "ХПИ", 2016)
На основе пространственного гармонического анализа магнитного поля в цилиндрической системе координат предложен метод расчета индукции магнитного поля линий электропередачи. Показано, что магнитное поле линий электропередачи с достаточной для инженерных расчетов точностью описывается первой цилиндрической пространственной гармоникой. Использование предложенного метода позволяет существенно упростить определение влияния конструкции опор линий электропередачи на величину их магнитного поля и на ширину полос отчуждения земельных участков

Simplification of accounting ratio to determine the magnetic field strength of electric power lines, and assessment of their environmental safety. Description of the transmission lines of the magnetic field by using techniques of spatial harmonic analysis in the cylindrical coordinate system is carried out. For engineering calculations of electric power lines magnetic field with sufficient accuracy describes their first spatial harmonic magnetic field. Substantial simplification of the definition of the impact of the construction of transmission line poles on the value of its magnetic field and the bands of land alienation sizes. Practical value. The environmentally friendly projection electric power lines on the level of the magnetic field.
Calculation method of electric power lines magnetic field strength based on cylindrical spatial harmonics
Keywords: ЛЭП; МП; охранные зоны; индукция; environmental safety